Karakačani v Bulharsku: Pastevecká historie - Fatková, Gabriela (Lidé města, 2011)
This article represents a synthesis of the studies on the former pastoral nomadic life of the Karakachans in Bulgaria, published in English and Bulgarian. The discussion on the origin of the Karakachans is analysed; there are various viewpoints, supported by various groups of researchers, by representatives of the Karakachans, as well as by the ordinary Karakachans themselves. The technology of transhuman pastoralism, related trade patterns, and the social structure of the Karakachan ethnic group in the pastoral nomadic period and at the end of this period, during sedentarization, is described.